To Pusa: Adaptasi, Respon, dan Stigma Terhadap Perempuan Muallaf di Desa Buntu Pepasan Toraja Utara - Moga, Arsih Susanti (Emik, 2025)
Converting to Islam is a form of religious conversion phenomenon that reflects the movement from one belief to another, in the context of this article, from Christianity to Islam. Although many studies have examined guidance and mentoring for converts, few (if any) have focused on the stigma against converts, especially female converts. This article fills this gap. This qualitative research was conducted in Buntu Pepasan Village, North Toraja. A total of 12 informants were involved in this study, consisting of eight women and four men, five of whom were converts, six families of converts, and one community leader. Data collection was carried out using in-depth interviews and observations. This study discusses how perceptions are related to converting. Some women converted to Islam based on personal beliefs and as an expression of religious freedom, others converted to Islam because of marriage. Converting to Islam not only has an impact on changes in spiritual beliefs, but it also has complex social consequences. In the new religion, they adapt in various aspects, namely: understanding Islamic teachings, eating habits, socializing, and changes in dress codes. They are socially ostracized from their families, but also excluded from customary rituals. However, it also highlights that female converts strive to practice Islam while maintaining ties with their families and cultural traditions. In addition, female converts are stigmatized with the term to pusa (heretics), who are considered to have deviated from ancestral values. The stigma against pusa is also combined with various negative terms such as to baga-baga (stupid people), to rokossik (naughty people), mariga-riga liu to pengauranmu (very dirty people), to natamai setang (people who are possessed by demons). However, the stigma against women who convert to islam is not directed at men. This is because a woman is a symbol of honor (siri’) for the family. Although they face serious challenges in the form of social stigma and identity conflicts, female converts show resilience and courage in living their new faith. This study emphasizes the importance of tolerance, respect for religious diversity, and the need for greater social support for converts. This study contributes to a deeper understanding of the complex relationships between religion, culture, and identity, particularly in the context of female converts in Indonesia's multicultural society.